Neighborhood effects on internalizing and externalizing problems, and academic competence: a comparison of Roma and non-Roma adolescents - Vazsonyi, Alexander T; Liu, Dan; Beier, Julia; Blatny, Marek (International journal of public health, 2020)
OBJECTIVES: The current study tested the extent to which the neighborhood context influenced Roma youth adjustment (internalizing and externalizing problems, and academic competence) and whether ethnicity moderated these links and explained unique variance. METHODS: Cross-sectional data were collected from 369 Roma and non-Roma early and middle adolescents. RESULTS: Roma youth reported significantly lower SES, school grades, and academic aspirations. Perceived fear or concerns about neighborhood safety predicted all three internalizing problems, for both Roma and non-Roma adolescents; neighborhood acquaintanceship density and nighttime social activities predicted externalizing behaviors, for both ethnic groups; and finally, both ethnicity and nighttime social activities predicted school grades, while only ethnicity predicted academic aspirations. No significant by ethnicity interaction effects were found. CONCLUSIONS: Roma youth reported lower grades and academic aspirations, but no mean level differences were found in internalizing or externalizing problems by ethnicity. On the other hand, neighborhood variables were important for both groups of youth, and with the exception of measures of academic competence, ethnicity did not explain unique variance. Thus, developmental processes, the links between neighborhood variables and measures of adjustment, were highly similar in Roma and non-Roma youth.
Keywords: Educational Status; Female; charakteristiky bydlení; etnicita; stupeň vzdělání; Ethnicity; ženské pohlaví; průřezové studie; Adolescent Behavior; Adolescent; lidé; Residence Characteristics; Cross-Sectional Studies; Male; Romové; Czech Republic; mladiství; Roma; Česká republika; Social Behavior; mužské pohlaví; White People; sociální chování; běloši; chování mladistvých; Humans